Prevalence and risk factors of post-kidney transplant hyperparathyroidism: a single-center study - O. N. Vetchinnikova; M. Yu. Ivanova (Вестник трансплантологии и искусственных органов)
Objective: to assess the prevalence of hyperparathyroidism (HPT) and the factors affecting its development in kidney transplant recipients. Materials and methods. The single-center observational cohort study included 97 kidney transplant recipients – 40 men, 57 women, age 50 ± 9 years. Inclusion criteria: more than 12 months of post-transplant period, 3 months of stable renal transplant function. Non-inclusion criterion: therapy with vitamin D, with its alternatives or with cinacalcet. Dialysis ranged from 0 to 132 months (median 18); 46% of patients had pre-operative secondary HPT. A comprehensive laboratory study included evaluation of serum concentrations of parathyroid hormone (PTH), 25-OH vitamin D, calcium, phosphorus, magnesium, total alkaline phosphatase (ALP) activity, albumin, creatinine and daily proteinuria. At the dialysis stage, the target PTH range of 130–585 pg/ ml was used, in the post-transplant period – ≤130 pg/ml. Glomerular filtration rate (eGFR) was calculated using the CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) formula. Results. Patients were divided into two groups based on PTH threshold level (130 pg/ml): the first with HPT (PTH >130 pg/ml, median 203), the second without HPT (PTH ≤130 pg/ml, median 101). Both groups were comparable in terms of gender, age, primary renal disease, dialysis modality, post-transplant follow-up, and immunosuppressive therapy regimen. In group 1 and group 2 recipients, dialysis therapy, pre-transplant median PTH level, incidence of reoperation and incidence of immediate renal graft function were 30 (14; 50) and 14 (6; 28) months (p = 0.004), 681 (538; 858) and 310 (182; 556) pg/ml (p < 0.001), 17% and 2% (p = 0.028), 51% and 80% (p = 0.005), respectively. At the time of the study, 72% of group 1 recipients had eGFR <60 ml/min, versus 36% of group 2 (p >< 0.001). Among HPT biochemical parameters, there were differences for ionized serum calcium (1.32 ± 0.07 versus 1.29 ± 0.04 mmol/l, p = 0.017) and ALP activity (113 ± 61 versus 75 ± 19 u/l, p = 0.021). Serum vitamin D in both groups reduced in equal measures – 14 ± 4 and 15 ± 6 ng/ml. Conclusion. Persistent HPT in the long-term post-transplant period reaches 48.5%. Risk factors for its development included dialysis for more than 18 months, pre-operative secondary HPT, repeated kidney transplantation, delayed graft function, and eGFR <60 ml/min.